2020
DOI: 10.1097/qai.0000000000002380
|View full text |Cite
|
Sign up to set email alerts
|

The Cascade of Care From Routine Point-of-Care HIV Testing at Birth: Results From an 18-Months Pilot Program in Eswatini

Abstract: Background: HIV testing at birth may improve early treatment, but concerns remain about feasibility and retention of infants in care. In 2017, point-of-care (POC) HIV birth testing was introduced into routine care at 3 high-volume maternity health facilities in Eswatini. Methods: POC birth testing was offered to HIV-exposed infants (HEI) born at, or presenting to, 3 maternities within 3 days of birth. Data were collected from a project-specific EID test request form and routine registers on all tests conducted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(28 citation statements)
references
References 18 publications
3
24
1
Order By: Relevance
“…Our data indicated that infants who received an at birth POC test were more likely to receive a second POC test by 12 weeks of age, compared to those who did not receive an at birth POC test. While a case-control study from South Africa indicated that high-risk infants who received at birth PCR testing were less likely to receive a repeat test than matched controls who did not receive an at birth test [19], our study and other similar studies from Eswatini, also did not support this finding [43]. Similarly, qualitative data suggests that mothers would find an initial negative result at birth encouraging and would motivate continued engagement in care [30].…”
Section: Plos Onecontrasting
confidence: 91%
See 1 more Smart Citation
“…Our data indicated that infants who received an at birth POC test were more likely to receive a second POC test by 12 weeks of age, compared to those who did not receive an at birth POC test. While a case-control study from South Africa indicated that high-risk infants who received at birth PCR testing were less likely to receive a repeat test than matched controls who did not receive an at birth test [19], our study and other similar studies from Eswatini, also did not support this finding [43]. Similarly, qualitative data suggests that mothers would find an initial negative result at birth encouraging and would motivate continued engagement in care [30].…”
Section: Plos Onecontrasting
confidence: 91%
“…This indicates that with minimal extra training and support, clinical staff already employed within the hospital can successfully process POC samples using GeneX. The at birth POC error rate observed in our study (8.5%) was higher than at 6 weeks (2.6%), however comparable to that observed in other studies (4.8%-11%) [17,27,43]. Higher error rates at birth could be a result of difficulty collecting adequate sample from infants.…”
Section: Plos Onesupporting
confidence: 82%
“…This study complements previous quantitative findings from the same overall study [14], and is a critical first step in understanding the value and feasibility of birth testing.…”
Section: Strengths and Limitationssupporting
confidence: 66%
“…More education and support are still needed, especially on the importance of treatment for positive infants, and about linkage to and continuation in care. Acceptance of birth testing was high, but quantitative data indicate a lower proportion of caregivers whose infants are immediately (within 14 days or diagnosis) started on ARVs [14]. This could be for multiple reasons, including the ease of an onsite test with no travel; the fact that the test is a one-time event unlike medications; the ability to test in secret without other family members; and that many women delivered alone and may have had autonomy to accept testing where they may not be able to accept medications once other family members are involved.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation